Strategies for Instilling Moral and Religious Values in Preventing Bullying Behavior at TK Doa Bunda Sungai Rumbai - Antika, Mira; Siska, Widia; Andre, Lesis; Afriwes, Afriwes (The Future of Education Journal, 2025)
The background of the problem in this study is that there is bullying behavior carried out by students at TK Doa Bunda Sungai Rumbai are in the from of verbal bullying, physical bullying, and relational bullying. The bullying cases that occur are such as between students pinching, kicking, hitting, nicknames, slander, ridicule, eye contact, sighs and sneers so that they cause discomfort for victims of bullying. This research is qualitative method. The objects of this research are 1 teachers, 1 principals, and 20 students at TK Doa Bunda Sungai Rumbai Dharmasraya Regency. Data collection is observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. Technique data validity is triangulation.The results of this study indicate that the forms of bullying carried out at Doa Bunda Sungai Rumbai Kindergarten are verbal, physical,and relational bullying with a total of 98 times. The most common form of bullying is verbal bullying 40 times with a percentage of 41%, consisting of 15 times of name calling, 6 times of slander, and 19 times of teasing. The form of physical bullying was carried out 38 times with a percentage of 39%, namely pinching 9 times, hitting 20 times, and kicking 9 times. Relational bullying was carried out 20 times with a percentage 20% consistingof 5 glances, 7 sighs, 8 taunts. The data shows that every day, the number of students who engage in bullying behavior decreases from the first day of the tenth study. Furthermore, this study also identifies strategies for instilling moral and religious values in preventing bullying behavior at Doa Bunda Sungai Rumbai Kindergarten, namely role model strategies, habitutation strategies, advice giving strategies, promise and threat giving strategies, and discipline strategies. Factors causing bullying behavior are influenced by family factors which are the main factors causing bullying in children, mass media factors, peer group factors or friends, and individual factors.